1992
DOI: 10.1901/jaba.1992.25-319
|View full text |Cite
|
Sign up to set email alerts
|

A Peer‐mediated Social Network Intervention to Enhance the Social Integration of Persons With Moderate and Severe Disabilities

Abstract: Increasingly, parents, teachers, and students with disabilities are advocating for interventions that go beyond skill training to provide support for participation in integrated environments and support for friendships. The present research demonstrated a social network intervention for youths with moderate and severe disabilities. Two groups of nondisabled peers were recruited to participate in weekly discussions with an adult integration facilitator to increase opportunities for social interaction for 2 stud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
127
0
3

Year Published

2000
2000
2017
2017

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 170 publications
(133 citation statements)
references
References 15 publications
3
127
0
3
Order By: Relevance
“…Group seating plans and group work activities often perpetuate the idea that typically developing peers who help students with disabilities, or merely sit next to them, are akin to "friends." Peer-mediated strategies have long been used by educators to increase the rate of social interaction by reinforcing and prompting a typically developing peer to initiate interactions or shape the social responding of a student with disabilities (Haring & Breen, 1992;DiSalvo & Oswald, 2002;McConnell, 2002). However, genuine friendships are those that translate into the after-school settings of home and community activities; peer-mediated strategies do not always see this translation materialize.…”
Section: Fostering Genuine Relationshipsmentioning
confidence: 99%
See 2 more Smart Citations
“…Group seating plans and group work activities often perpetuate the idea that typically developing peers who help students with disabilities, or merely sit next to them, are akin to "friends." Peer-mediated strategies have long been used by educators to increase the rate of social interaction by reinforcing and prompting a typically developing peer to initiate interactions or shape the social responding of a student with disabilities (Haring & Breen, 1992;DiSalvo & Oswald, 2002;McConnell, 2002). However, genuine friendships are those that translate into the after-school settings of home and community activities; peer-mediated strategies do not always see this translation materialize.…”
Section: Fostering Genuine Relationshipsmentioning
confidence: 99%
“…Among the strategies/accommodations that an educational assistant can provide for a student with ASD in the classroom are: -Increasing physical proximity to peers -Fading assistance to allow for more natural peer interaction opportunitiesPartnering student with ASD with peers during academic tasks -Verbally highlighting similarities between student with ASD and peers -Creating communication cards focused on social exchanges -Teaching peers how to communicate with target student using sign language gestures -Utilizing interactive technology -Giving student with ASD classroom responsibilities that encourage interaction with peers (Causton-Theoharis, J., & Malmgren, 2005, p. 436) Social skills training programs are another possible response to the need for individualized training in reciprocal play and conversational skills for children with ASD. While social skills training programs have been shown to have a positive effect on problem-solving skills in children with ASD (Embregts & van Nieuwenhuijzen, 2009;McConnell, 2002;Wolfberg & Schuler, 1993), these programs can lack social validity in terms of generalization of skills outside of the training sessions (Haring & Breen 1992;Ozonoff & Miller, 1995). Haring and Breen (1992) found that social skills training packages, while useful in terms of determining existing levels of social competence, may not translate into friendship relationships outside of the training context.…”
Section: Fostering Genuine Relationshipsmentioning
confidence: 99%
See 1 more Smart Citation
“…Intervention has been found to be more successful when peer ownership, and problem solving were emphasised over teachermediated strategies [9,10,12,13] . For one of the students in this study, the group facilitator attempted to mediate informal meetings between the target student and peers from the secondary school for after school meetings at a local teashop; however these were also unsuccessful and did not occur.…”
Section: Jeanne D'haemmentioning
confidence: 99%
“…Nevertheless, peers rarely are involved in social skills programs (Haring & Breen, 1992). Therefore, lack of generalization to peers following social interaction interventions should not be surprising (Chandler et al, 1992).…”
mentioning
confidence: 99%